Relações de trabalho : o sentido da subordinação e as novas formas de trabalho - Souza, Jonatan Teixeira de (2021)
Subordination is a defining requirement of employment relationships, as it is the one that best differentiates this type of contract from other forms of work. However, the evolution of technology has brought great changes in the way of working, which impacts, in a similar way, in the sense attributed to subordination by Brazilian doctrine and jurisprudence. While some authors maintain that the transformations of technology should expand the sense of subordination, in order to encompass many labor relations in which there is no certainty as to the effective subjection of the worker to the service taker, part of the doctrine and jurisprudence understands that the new forms of work restrict the sense of subordination, which must be limited to contracts in which the provision of work is similar to the Fordist-Taylorist production system. The present work finds that the sense of subordination tends to be restricted, in the light of the provisions of Law No. 13.467 / 2017 and the technological context that involves labor relations.